The Effects of Advertising on Facebook on Admission Interests in Higher Education - Surahmat, Surahmat; Putro, Rochid Tri Hanggoro; Nugraha, Lintang Hakim (Lembaran Ilmu Kependidikan, 2020)
This research was conducted to examine the effects of advertising on Facebook to increase admission interest in higher education, particularly Universitas Negeri Semarang. Using the experimental research method, the researchers posted two advertisements with different formats at different times on Facebook to measure the engagement score and its effects on student admission. Research results showed that each of the ads performed differently according to their formats. Image-based ad had a greater engagement score of 0.0065 compared to video-based ad which had only 0.0017. Both image-based and video-based ads attracted more female users than male users. The ads also showed a possitive effects on increasing visits to the registration site of Universitas Negeri Semarang (penerimaan.unnes.ac.id). There was no reliable evidence, however, that could show the direct effectiveness of advertising on Facebook to increase university admission. That said, further research is needed to fully answer this research question.